Correction: Recent advances in air electrodes for Zn–air batteries: electrocatalysis and structural design. Issue 3 (29th March 2018) - Cai, Xiaoyi; Lai, Linfei; Lin, Jianyi; Shen, Zexiang
Abstract : Correction for 'Recent advances in air electrodes for Zn–air batteries: electrocatalysis and structural design' by Xiaoyi Cai et al., Mater. Horiz., 2017, 4, 945–976.